Context-perception model of third language learning motivation - Matsumoto, Masanori (Journal of Modern Languages, 2017)
Through Matsumoto’s recent studies (2009, 2011) on foreign language learners’ motivation in Australian context, a third cultural factor has been detected. Both studies have revealed that besides the conventional account of the cultural distance between learners’ own culture and that of target language, the distance between learners’ own culture and the Australian educational culture in which their language learning occurs also influences the learners’ motivational state. That is, when learners learn a second foreign language in the second language educational context, this additional third culture plays an additional role which affects learner motivation. The study of cultural distance as a factor affecting motivation further must consider student perceptions of learning events, because they perceive the same learning and environmental factors differently according to their cultural backgrounds. As a result, their appraisals of events affect their motivation. Based on these considerations, a new framework of third language (L3) learning motivation is proposed and discussed.